(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
In recent years, the integration of language skills into medical care has transformed traditional healthcare methodologies. This study examines the impact of foreign languages—such as Russian, English, German, and Turkish—on medical careers. The research adopts a mixed-methods approach, incorporating both quantitative assessments and qualitative feedback from polyclinic doctors. Results indicate that the knowledge of language enhances doctor motivation, promotes attending international conferences and trainings, and supports communicative competence. The study concludes with practical solutions and recommendations for the easy learning of languages.